Quercetin Alleviates Lipopolysaccharide-Induced Inflammatory Response in Bovine Mammary Epithelial Cells by Suppressing TLR4/NF-κB Signaling Pathway - Jiang, Maocheng; Lv, Ziyao; Huang, Yinghao; Cheng, Zhiqiang; Meng, Zitong; Yang, Tianyu; Yan, Qi; Lin, Miao; Zhan, Kang; Zhao, Guoqi (Frontiers in Veterinary Science, 2022)
Bovine mastitis is one of the most common clinical diseases in dairy cows, causing huge economic losses to the dairy industry. Quercetin is an important flavonoid existing in many food resources, which has attracted widespread attention as a potential anti-inflammatory and antioxidant. However, the molecular mechanism of quercetin on inflammatory responses and oxidative stress in bovine mammary epithelial cells (BMEC) induced by lipopolysaccharide (LPS) that remains not known. The objective of this study was to investigate the effect of quercetin on inflammation responses, oxidative stress, and barrier function of BMEC induced by LPS. Our results showed that BMEC viability was not affected by treatment with 50 and 100 μg/mL quercetin and 1μg/mL LPS compared with control group. The results of oxidative stress indicators and related genes of barrier function indicated that 100 μg/mL quercetin effectively protected BMEC from damage of oxidative and barrier induced by 1 μg/mL LPS. Moreover, the mRNA expression of pro-inflammatory cytokines TNF-α, IL-1β, IL-6 and chemokines CXCL2, CXCL5, CCL5 and CXCL8 were markedly decreased in the LPS-treated BREC with 100 μg/mL quercetin relatively to LPS alone. More importantly, mRNA expression of toll-like receptor 4 (TLR4), CD14, myeloid differential protein-2 (MD2), and myeloid differentiation primary response protein (MyD88) genes involved in TLR4 signal pathway were significantly attenuated by the addition of quercetin in LPS-treated BMEC, suggesting that quercetin can inhibit the TLR4 signal pathway. In addition, immunocytofluorescence showed that quercetin significantly inhibited the nuclear translocation of NF-κB p65 in BMEC induced by LPS. Therefore, the protective effects of quercetin on inflammatory responses in LPS-induced BMEC may be due to its ability to suppress the TLR4-mediated NF-κB signaling pathway. These findings suggest that quercetin can be used as an anti-inflammatory reagent to treat mastitis induced by exogenous or endogenous LPS release.